Feeling of women regarding the use of the Billings Ovulation Method - Eliane Vieira dos Santos; Rita de Cássia Maria dos Santos Frazão; Sheyla Costa de Oliveira (Rev Rene)
Objective: to know the feelings of women regarding the use of the Billings Ovulation Method as family planning. Methods: a qualitative study was carried out with eight women through a semi-structured interview and data were analyzed through the thematic analysis. Results:the results were organized into four main thematic categories: Use of the method and self-knowledge of the body; Insecurity as to the use of the method; Choice based on religious principles; and Complicity of the couple in the execution of the method. Conclusion:participants using the Billings Ovulation Method were satisfied and safe, and the participation of the partner was critical to the use of the method as natural family planning.